Hak-Hak Tahanan dan Narapidana di Rumah Tahanan Negara - Kamel, Rusli; Malik, Faissal; Anshar, Anshar (Legal Spirit, 2024)
Human Rights are inherent to every individual, yet there are circumstances and time frames where these rights may be restricted or revoked by the state in accordance with applicable rules. One such circumstance is being incarcerated or imprisoned because of unlawful acts committed by individuals. The research aims to identify the impact of overcrowded prison conditions on the fulfillment of rights for detainees and inmates within the Class IIB State Detention Center in Ternate. Additionally, it seeks to analyze the legal implications of overcrowded conditions on the satisfaction of these rights. The findings indicate that overcrowding adversely affects the fulfillment of basic needs for detainees and inmates, including physical and spiritual care, health services, and provision of adequate food. Legal implications concerning the handling of overcrowded conditions in Ternate Detention Center, as mandated by the Ministry of Law and Human Rights of the Republic of Indonesia through Regulation No. 11 of 2017, have not effectively addressed the challenges posed by overcrowded conditions. Limitations in human resources, insufficient living space, inadequate infrastructure, and budget constraints in Ternate Detention Center hinder the optimization of meeting the rights of Persons Deprived of Liberty (WBP).